COMPREHENSIVE EDUCATIONAL AND METHODOLOGICAL SUPPORT OF THE EDUCATIONAL PROCESS IN TEACHING THE RUSSIAN LANGUAGE: CONCEPT, ESSENCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The characteristic features of the reform and modernization of education in Uzbekistan are the desire to improve the quality of education, fundamentality and integration, strengthening the humanistic focus, increasing variability, the role of independent work of students and technologization of the learning process. The goal of informatization is to create conditions for the development of the individual, his/her self-determination and self-realization. The educational process in the educational institution is aimed at achieving this goal. The main purpose of this article is to find some solutions to develop and create an educational and methodological complex on the basics of logic for first-year students in institute.